(untitled) (Texas Journal of Medical Science, 2023)
One hundred (100) patients were collected from different hospitals in Iraq, and a cross-sectional study was designed using an electronic system) what is the name of the system) of samples that were evaluated and approved by the competent committees in Iraq? The population included in the study was residents of Baghdad, Muthanna, and Basrah Governorates who voluntarily agreed to participate from 5 years to 45 years of age and indicated that those under 18 years of age should obtain permission from their parents or legal guardians (expressing consent in an e-mail form prior to arrival to the exploratory study). The data collected by in this research, the questionnaire, which was designed based on a number of sections, including the age of patients, in addition to the variables associated with smart phone devices and visual symptoms to the eyes. Demographic data related to the patients were also analyzed by relying on the IBM SOFT SPSS program. The patients were classified into two groups (60 patients and 40 control). The period of time the patient spent on the phone was 4.3±1.9 for the patient and 3.5±1.1 for the control in this study, the assessment according to dry eye severity (for mild, 10 (16.6), control 26 (65)-Moderate for patient 33 (55), control 8 (20)-Severe Irreversible damage to the ocular surface Plus for patient 17 (28.3), control 6 (15) with p-value <0.05 Complications found in this study include Conjunctivitis, Keratitis, Corneal ulcer, Inability to wear contact lenses, Damage to the surface of eyes, decreased quality of life, and Photophobia for 40 patients and 17 control. Statistical analysis program was used to find out the type of statistical relationship emerging between the time spent using smartphones and dry eyes, where person correlation was used at a statistical significance level at p-value <0.001, while in this study, it was found that there is a direct relationship between the Time spent to use a phone with dry eyes